Mechanism of crocin I on ANIT-induced intrahepatic cholestasis by combined metabolomics and transcriptomics - Song, Dandan; Zhu, Pei; Dong, Yankai; Wang, Mengchao; Zhao, Anna; Xia, Hongdong; Chen, Yunting; Zhou, Qingguang; Xiang, Lun; Zhang, Junyi; Luo, Guangming; Luo, Yangjing (Frontiers in Pharmacology, 2023)
Background: Intrahepatic cholestasis (IC) is a disorder of bile production, secretion, and excretion with various causes. Crocin I (CR) is effective in the treatment of IC, but its underlying mechanisms need to be further explored. We aimed to reveal the therapeutic mechanism of crocin I for IC by combining an integrated strategy of metabolomics and transcriptomics. Methods: The hepatoprotective effect of CR against cholestasis liver injury induced by α-naphthylisothiocyanate (ANIT) was evaluated in rats. The serum biochemical indices, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bile acid (TBA), total bilirubin (TBIL), direct bilirubin (DBIL), tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), and interleukin 1β (IL-1β), as well as the liver oxidative stress indexes and the pathological characteristics of the liver were analyzed. In addition, we also performed a serum metabolomics study using UPLC-Q Exactive HF-X technology to investigate the effect of CR on the serum of rats with ANIT-induced IC and screened potential biomarkers. The enrichment analysis of differential expressed genes (DEGs) was performed by transcriptomics. Finally, the regulatory targets of CR on potential biomarkers were obtained by combined analysis, and the relevant key targets were verified by western blotting. Results: CR improved serum and liver homogenate indexes and alleviated liver histological injury. Compared with ANIT group, the CR group had 76 differential metabolites, and 10 metabolic pathways were enriched. There were 473 DEGs significantly changed after CR treatment, most of which were enriched in the retinol metabolism, calcium signaling pathway, PPAR signaling pathway, circadian rhythm, chemokine signaling pathway, arachidonic acid metabolism, bile secretion, primary bile acid biosynthesis, and other pathways. By constructing the “compound-reaction-enzyme-gene” interaction network, three potential key-target regulation biomarkers were obtained, including 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR), ATP-binding cassette transporter G5 (ABCG5), and sulfotransferase2A1(SULT2A1), which were further verified by western blotting. Compared with the ANIT group, the CR group significantly increased the expression of ABCG5 and SULT2A1, and the expression of HMGCR significantly decreased. Conclusion: Combined metabolomic and transcriptomic analyses show that CR has a therapeutic effect on IC through regulation of the biosynthesis of bile acids and bilirubin in the bile secretion pathway and regulation of the expression of HMGCR, ABCG5, and SULT2A1.